A Review on Exosome Based Drug Delivery System (International Journal of Research in Pharmaceutical Sciences and Technology, 2026)
Because of their natural origin, superior biocompatibility, and inherent capacity to facilitate intercellular communication, exosome-based drug delivery systems have become a new and promising platform in nanomedicine. Extracellular vesicles [30 to 150 nm] called exosomes are released by almost every type of cell and can be found in a variety of bodily fluids, such as urine, saliva, and blood. They transport a complex cargo of lipids, proteins, and genetic elements like miRNA and mRNA transcripts, which are essential for controlling biological and disease related processes. These biological vesicles have distinct benefits over manufactured nanoparticles, such as their high stability, minimal immunogenicity, effective cellular absorption, and capacity to pass through biological membranes that provide protection. Exosomes have drawn a lot of attention lately as natural carriers of therapeutic molecules, like as proteins, nucleic acids, and tiny medicines, for the treatment of diseases like cancer, neurological disorders, and cardiovascular disorders. Exosomes' targeting effectiveness and therapeutic potential have been improved by sophisticated methods in exosome extraction, purification, and engineering, including as surface modification and cargo loading. All things considered, exosome-based drug delivery systems offer a state-of-the-art, biocompatible, and adaptable approach to precise, targeted, and customized therapy in contemporary biomedical research. Current review focuses on types of exosomes, the biology and biogenesis of exosomes, isolation and characterization of exosomes.
Keywords: Exosomes; Isolation; Characterization; Biogenesis